EMPLOYEE PARTICIPATION IN DECISION-MAKING AND PERCEIVED ORGANIZATIONAL SUPPORT AS PREDICTORS OF ORGANIZATIONAL CITIZENSHIP BEHAVIORS - Philip Adekanmbi, Foluso; I. Ukpere, Wilfred (International Journal of Psychosocial Rehabilitation, 2021)
In response, employees put in additional effort within an organization as they perceive that the organization provides opportunities, resources, and fair treatment based on the standard of exchange. Drawing on need theory, social exchange theory, and the two-factor theory, this paper examines the influence of employee participation in decision-making (EPDM) and perceived organizational support (POS) on organizational citizenship behaviors (OCBs) within selected business organizations. The study’s sample was drawn from 12 selected business organizations across some southwestern states (Lagos, Oyo, and Ogun) of Nigeria. A quantitative research approach was adopted, and questionnaires were randomly distributed. Out of 600 questionnaires, 569 were useful for analysis after processing the data with SPSS version 26. The paper showed that employee participation in decision-making and perceived organizational support significantly and positively predict organizational citizenship behaviors within business organizations. Further investigation revealed that age significantly and positively predicts organizational citizenship behaviors, while an employee’s educational qualification significantly and negatively predicts organizational citizenship behaviors. Therefore, organizational managers and human resources practitioners should encourage employees’ organizational citizenship and discretionary behaviors that promote organizational success. Additionally, they should work towards reducing negative stereotyping of older workers.